Penilaian Kinerja Pada Karyawan Milenial Di Kantor PT. PLN (Persero) ULP Taman - Jaelani, Muhammad Noer Qamaruddin; Rahim, Ahmad Ghulam Amrullah; Wahjono, Sentot Imam (Innovative: Journal Of Social Science Research, 2024)
This study aims to analyze the impact of work engagement, flexibility, and feedback on the performance of millennial employees at PT. PLN (Persero) ULP Taman. Using a survey method with 100 respondents, the research found that work engagement has the most significant influence (β = 0.52), followed by flexibility (β = 0.40) and feedback (β = 0.38). The results indicate that millennial employees who are actively engaged in their work and receive adequate flexibility demonstrate higher performance. Recommendations are made to enhance engagement programs and feedback systems to support the performance of millennial employees.